Psychological features of teachers «Professional burnout» manifestation - Galyna Fesun; Yuliia Zhurat (Journal of Research and Innovation for Sustainable Society)
The article presents the results of "professional stress" theoretical and empirical study whichis a multidimensional phenomenon expressed in physiological and psychological reactions to a difficult professional situation. The syndrome of "professional burnout" as a consequence of long-term professional stress of medium intensity is considered. The structure of the "professional burnout" syndrome is determined as a three-component system based on the researches of K. Maslach and S. Jackson, which includes emotional exhaustion, depersonalization, and reduction of personal achievements. As well as on V. Boyko’s definition, which includes such components as tension, resistance, exhaustion in the structure of the syndrome.